Mahonia vs. Berberis Unloaded: Generic Delimitation and Infrafamilial Classification of Berberidaceae Based on Plastid Phylogenomics - Hsieh, Chia-Lun; Yu, Chih-Chieh; Huang, Yu-Lan; Chung, Kuo-Fang (Frontiers in Plant Science, 2022)
The early-diverging eudicot family Berberidaceae is composed of a morphologically diverse assemblage of disjunctly distributed genera long praised for their great horticultural and medicinal values. However, despite century-long studies, generic delimitation of Berberidaceae remains controversial and its tribal classification has never been formally proposed under a rigorous phylogenetic context. Currently, the number of accepted genera in Berberidaceae ranges consecutively from 13 to 19, depending on whether to define Berberis, Jeffersonia, and Podophyllum broadly, or to segregate these three genera further and recognize Alloberberis, Mahonia, and Moranothamnus, Plagiorhegma, and Dysosma, Diphylleia, and Sinopodophyllum, respectively. To resolve Berberidaceae’s taxonomic disputes, we newly assembled 23 plastomes and, together with 85 plastomes from the GenBank, completed the generic sampling of the family. With 4 problematic and 14 redundant plastome sequences excluded, robust phylogenomic relationships were reconstructed based on 93 plastomes representing all 19 genera of Berberidaceae and three outgroups. Maximum likelihood phylogenomic relationships corroborated with divergence time estimation support the recognition of three subfamilies Berberidoideae, Nandinoideae, and Podophylloideae, with tribes Berberideae and Ranzanieae, Leonticeae and Nandineae, and Podophylleae, Achlydeae, Bongardieae tr. nov., Epimedieae, and Jeffersonieae tr. nov. in the former three subfamilies, respectively. By applying specifically stated criteria, our phylogenomic data also support the classification of 19 genera, recognizing Alloberberis, Mahonia, and Moranothamnus, Plagiorhegma, and Diphylleia, Dysosma, and Sinopodophyllum that are morphologically and evolutionarily distinct from Berberis, Jeffersonia, and Podophyllum, respectively. Comparison of plastome structures across Berberidaceae confirms inverted repeat expansion in the tribe Berberideae and reveals substantial length variation in accD gene caused by repeated sequences in Berberidoideae. Comparison of plastome tree with previous studies and nuclear ribosomal DNA (nrDNA) phylogeny also reveals considerable conflicts at different phylogenetic levels, suggesting that incomplete lineage sorting and/or hybridization had occurred throughout the evolutionary history of Berberidaceae and that Alloberberis and Moranothamnus could have resulted from reciprocal hybridization between Berberis and Mahonia in ancient times prior to the radiations of the latter two genera.